Jules Dassin's Rififi - Auric, Georges 1899-1983 (The Criterion Coll., 2001)
A story of a successful jewel robbery in which the four thieves betray each other.
Bildformat 1.33:1 aspect ratio
Orig.: Frankreich 1955
Enth. exclusive video interview with director Jules Dassin ; production stills, plus set design drawings by Alexandre Trauner ; production notes
Keywords: Feature films; Gangster films